Biocompatible Gelatinized Starch as a Functional Modulator to Expand the Scope of Injectable Hydrogels - Hangyu Li; Jingwen Wang; Xiushuai Shang; Xiaotian Su; Iek Man Lei; Xulin Hu; Yihe Hu; Shuai Li (Advanced Healthcare Materials, 2026)
ABSTRACT Injectable hydrogels used in tissue engineering and minimally invasive therapies are limited by insufficient biocompatibility, poor scalability, high costs, and inconsistent performance. Here, we introduce gelatinized starch, a common polysaccharide, as a versatile and economical building block to expand the existing repertoire of injectable hydrogel materials. Derived from native corn starch via heating and gelatinization, this biopolymer exhibits shear‐thinning, thixotropic, and thermoreversible sol–gel transition properties, key rheological characteristics essential for syringeability and in situ structural recovery. It readily integrates with photo‐crosslinkable (e.g., GelMA, HAMA, AlgMA) and ionically crosslinkable (e.g., alginate, chitosan) hydrogels. Rheological tests confirm that starch incorporation imparts excellent injectability, rapid gelation, and robust structural recovery. Bone marrow mesenchymal stem cells (BMSCs) encapsulated in starch‐based composite hydrogels maintained high viability, showed enhanced protein expression, and exhibited strong proliferation, which were modulated by starch concentration and cell seeding density. Notably, injection depth influenced post‐delivery cell viability within the hydrogel, whereas injection width had no significant effect. In a rat femoral condyle defect model, injection of a BMSC‐laden gelatinized starch hydrogel markedly promoted bone regeneration. Collectively, gelatinized starch overcomes key limitations of conventional injectable hydrogels, providing a cost‐effective, biocompatible, and functionally adaptable platform for cell delivery and tissue regeneration.